2009
DOI: 10.1093/aje/kwp019
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effect of Cigarette Smoking With Human 8-Oxoguanine DNA N-Glycosylase 1 (hOGG1) Polymorphisms on the Risk of Lung Cancer: A Case-Control Study in Taiwan

Abstract: Human 8-oxoguanine DNA N-glycosylase 1 (hOGG1) plays an important role in repairing oxidative DNA damage induced by tobacco carcinogens. In this case-control study, the authors examined the interactive effect of hOGG1 gene polymorphisms and cigarette smoking on the risk of lung cancer in Taiwan. A total of 1,096 cases and 1,007 controls were enrolled from 6 medical centers in Taiwan during 2002-2004. hOGG1 Ser326Cys genetic polymorphisms were determined using the MassARRAY system (SEQUENOM, Inc., San Diego, Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 25 publications
6
31
0
Order By: Relevance
“…The mean age of our lung cancer patients at recruitment was 66.2 years was also comparable to that found in a previous study for Taiwanese (63.4 years) [35]. In addition, prevalence of cigarette smoking in our study subjects (cases, 54.1%; controls, 27.1%) was consistent with the findings of a previous study in Taiwanese (cases, 52.4%; controls, 29.9%) [36]. Therefore, our study subjects could be regarded to as representative of the general population of Taiwan.…”
Section: Discussionsupporting
confidence: 90%
“…The mean age of our lung cancer patients at recruitment was 66.2 years was also comparable to that found in a previous study for Taiwanese (63.4 years) [35]. In addition, prevalence of cigarette smoking in our study subjects (cases, 54.1%; controls, 27.1%) was consistent with the findings of a previous study in Taiwanese (cases, 52.4%; controls, 29.9%) [36]. Therefore, our study subjects could be regarded to as representative of the general population of Taiwan.…”
Section: Discussionsupporting
confidence: 90%
“…The risk of lung cancer among Henanese with Cys/Cys is 2.12 (1.03 -4.39) times high of that among Henanese with Ser/Ser or Ser/Cys genotype. Thess results are sinliar with the previous studies (Chang et al, 2009;Liu et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies demonstrated that genetic variation in OGG1 affects cancer susceptibility; the frequency of the OGG1 326Cys allele was found to be significantly higher in patients when compared with controls [22], [24], [25], [37], [38]; however, this association was not replicated by other studies [9], [13][17]. Overall, we did not found that individuals carrying the Cys/Cys genotype had significantly increased risk of lung cancer when compared with the Ser/Ser genotype, no significant association with lung cancer risk was found in dominant model, recessive model and heterozygous co-dominant model (Ser/Cys vs. Cys/Cys).…”
Section: Discussionmentioning
confidence: 98%